Bulky Vehicles Recycling. Part 2 - Recycling of Selected Vehicle Components - Anna Matuszewska; Piotr Wieczorek; Marlena Owczuk (Studia Ecologiae et Bioethicae)
Recycling of end-of-life passenger vehicles is a well-known topic, and there are many literary reports in this regard. However, little information is available on the recycling of bulky vehicles, which determines the authors’ intention to present this issue. The article describes the recycling methods for selected components (tires, windows, catalytic converters, polymer and metal materials, operating fluids), with an indication of the differences between heavy goods vehicles and passenger cars. Examples of large corporations producing vehicles, whose activities facilitate the recycling and segregation of materials used in bulky vehicles, are presented. These corporations meet the changes taking place, and implement the principles of the circular economy, in the field of recycling large-size vehicles. It has been shown that there are still many challenges in the field of vehicle recycling, in particular, with regard to composite materials, and for some recycling technologies, there is still a lack of adequate infrastructure in Poland.